Molecular dynamics simulations of defective carbon nanotubes on the aging and friction properties of nitrile butadiene rubber composites. Issue 2 (17th November 2022) - Wang, Mengjia; Li, Yunlong; Qian, Cheng; Zhao, Jing; Wang, Shijie
Abstract: The thermal‐oxidative aging (TOA) and tribological properties of rubber had attracted attention in the petrochemical field. In this study, the mechanical and tribological properties of defect‐free, Stone–Wales (SW), and single adatom (SA) defective carbon nanotubes (CNTs)/nitrile butadiene rubber (NBR) composites were investigated using molecular dynamics simulations. Poly (1, 2‐dihydro‐2, 2, 4‐trimethyl‐quinoline) (antioxidant RD) was added to the composites to analyze their TOA mechanisms. Antioxidant RD provided the best protective effect in SW‐CNTs/RD/NBR composites, and their TOA properties were enhanced. In addition, the Young's modulus, bulk modulus, and shear modulus, friction coefficient, and wear rate of the SW‐CNTs/RD/NBR composites were improved. The effects of SW‐CNTs on the RD/NBR composites were elucidated from a molecular perspective. The surface structures of three groups of CNTs were analyzed, and the SW‐CNTs exhibited a stronger adsorption ability and binding effect. It was determined that the antioxidant RD and NBR could be more stably dispersed between the molecular chains in the SW‐CNTs/RD/NBR composites. Abstract : Molecular modeling of defective carbon nanotubes, RD antioxidants, nitrile butadiene rubber and mechanical properties.